2016
DOI: 10.5993/ajhb.40.4.8
|View full text |Cite
|
Sign up to set email alerts
|

User-centered Design of a Texas WIC App: A Focus Group Investigation

Abstract: The enthusiasm of focus group participants for a comprehensive WIC app suggests that this initiative is timely, and that an app has potential to improve health behaviors. Future research should continue the user-centered design process through further evaluation of prototype features, incorporating cultural preferences at every step.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 0 publications
2
38
0
Order By: Relevance
“…Other research, however, has suggested several ways in which standard smartphone features or nonhealth apps can serve health purposes. These include alarms [28], Web searches [29], calendar apps [30], and social media [30-32]. This is consistent with some of the apps reported by our participants, such as Google Sheets, which one participant used for migraine tracking.…”
Section: Discussionsupporting
confidence: 83%
“…Other research, however, has suggested several ways in which standard smartphone features or nonhealth apps can serve health purposes. These include alarms [28], Web searches [29], calendar apps [30], and social media [30-32]. This is consistent with some of the apps reported by our participants, such as Google Sheets, which one participant used for migraine tracking.…”
Section: Discussionsupporting
confidence: 83%
“…Nine studies were identified reporting user-testing by parents of digital health tools targeting improvements in children's nutrition. Five evaluated apps [18,[40][41][42][43], three evaluated websites [19,39,44] and one evaluated both an app and website [45] (Table 2; Additional file 3). Studies were conducted in the USA [41][42][43][44], Australia [18,19,45], Canada [40] and Switzerland [39].…”
Section: Objective Twowhat Do Parents Want From Digital Tools Supportmentioning
confidence: 99%
“…Five evaluated apps [18,[40][41][42][43], three evaluated websites [19,39,44] and one evaluated both an app and website [45] (Table 2; Additional file 3). Studies were conducted in the USA [41][42][43][44], Australia [18,19,45], Canada [40] and Switzerland [39]. Evaluations of preferences for content, features, technology, delivery mode, useability and barriers were conducted using focus groups [39][40][41][42]44] and questionnaires [18,19,39,41,43,45].…”
Section: Objective Twowhat Do Parents Want From Digital Tools Supportmentioning
confidence: 99%
See 2 more Smart Citations